Hard boys, attractive girls: expressions of gender in young people's conversations on smoking in Northern Ireland. - Rugkåsa, J; Stewart-Knox, B; Sittlington, J; Abaunza, P; Treacy, M (2003)
Health behaviour and attitudes among young people can be interpreted within the context of personal and social identity. This paper explores ways in which 10- to 11-year-olds in Northern Ireland expressed perceptions of gender ideology while discussing the topic of smoking. The data were gathered by means of in-depth interviews (n=85). Although few had tried smoking, the positive quality of their own gender appeared to be expressed through negative assessment of smokers of the opposite gender, and on different ideas of perceived gender dimensions in adult smoking. In order to deliver successful health promotion interventions, it is crucial to understand and address differences based on gender as it may partly explain differences in smoking experimentation and prevalence.